2013
DOI: 10.1002/grl.50813
|View full text |Cite
|
Sign up to set email alerts
|

Microslips as precursors of large slip events in the stick‐slip dynamics of sheared granular layers: A discrete element model analysis

Abstract: [1] We investigate the stick-slip behavior of a granular system confined and sheared by deformable solid blocks using three-dimensional discrete element method simulations. Our modeling results show that large slip events are preceded by a sequence of small slip eventsmicroslips-whose occurrence accelerates exponentially before the large slip event onset. Microslips exhibit energy release several orders of magnitude smaller than the large slip events. The microslip event rate is proposed as a measure of slip a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
65
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 38 publications
(46 reference statements)
7
65
0
1
Order By: Relevance
“…The sample size in our simulations is 11 × 1.5 × 0.8 mm that is equivalent to 6.7 d p in depth (direction y in Figure ), 12.5 d p in height (direction z in Figure ), and 91.7 d p in length (direction x in Figure ), respectively, where d p is mean particle diameter, 120 μm. We remark that as a guideline, previous numerical simulations have shown that the nature of stick‐slip dynamics and distribution of slip event size remains almost unchanged for different sample sizes if appropriate size (equal to or bigger than 4 d p ) is produced in depth of such granular fault gouge [ Ferdowsi et al ., ; Ferdowsi , ].…”
Section: Numerical Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…The sample size in our simulations is 11 × 1.5 × 0.8 mm that is equivalent to 6.7 d p in depth (direction y in Figure ), 12.5 d p in height (direction z in Figure ), and 91.7 d p in length (direction x in Figure ), respectively, where d p is mean particle diameter, 120 μm. We remark that as a guideline, previous numerical simulations have shown that the nature of stick‐slip dynamics and distribution of slip event size remains almost unchanged for different sample sizes if appropriate size (equal to or bigger than 4 d p ) is produced in depth of such granular fault gouge [ Ferdowsi et al ., ; Ferdowsi , ].…”
Section: Numerical Setupmentioning
confidence: 99%
“…The nature of stress accommodation and the dynamics of the stick‐slip events have been well studied in laboratory experiments and numerical simulations primarily on dry granular fault gouge [ Marone , , ; Morgan , ; Mair et al ., ; Guo and Morgan , ; Anthony and Marone , ; Johnson and Jia , ; Mair and Hazzard , ; Johnson et al ., ; Samuelson et al ., ; Johnson et al ., ; Johnson et al ., ]. Recent 3‐D discrete element method (DEM) numerical simulations of dry granular fault gouge demonstrate both spontaneous and triggered stick‐slip [ Ferdowsi et al ., ; Griffa et al ., ; Ferdowsi et al ., , ] similar to experiments. There exist a few studies of fluid‐saturated granular fault gouge as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These experiments were accompanied by numerical models mainly using the discrete element method (e.g. Abe and Mair, 2009;Abe et al, 2006;Ferdowsi et al, 2013Ferdowsi et al, , 2014Ferdowsi et al, , 2015Mair and Abe, 2008;Mair and Hazzard, 2007). The shearing of optically clear acrylic or polymeric spheres and discs (e.g.…”
Section: Spring-slider Modelsmentioning
confidence: 99%
“…Indeed, the resistance to shear stress of seismic faults is typically much larger than the one obtained in experiments measuring the friction coefficient of sliding rocks [15]. Furthermore, remote triggering of earthquakes [16][17][18][19][20] at distances of thousand kilometers from the main shock epicenter indicates a high susceptibility of seismic faults to the passage of seismic waves. The hypothesis of Acoustic Fluidization (AF), formulated by Melosh [21,22], provides an answer to both questions.…”
mentioning
confidence: 99%